2021
DOI: 10.2478/plua-2021-0003
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Optimization of Feeding Device Parametres in the Plant for Preparing Liquid Feed Mixtures

Abstract: Feeding young animals is a very important stage during their growing-up period, but in order to provide them with essential nutrients, they are fed with liquid feeds, whole milk substitute in particular (WMS). The technique for reconstituting WMS consists of dissolving it in water followed by mixing, but it is significant to follow the cooking recipe strictly, so it is necessary to develop a system with a feeding (dosing) device that will make it possible to solve this problem. Theoretical and experimental stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is based on two main properties of a liquid medium: continuity and continuous change of flow parameters in the volume under consideration. Therefore, for the calculation, we use a methodology for determining the size of the impeller and the inlet diameter, in relation to the installation for the preparation of liquid feed mixtures [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…It is based on two main properties of a liquid medium: continuity and continuous change of flow parameters in the volume under consideration. Therefore, for the calculation, we use a methodology for determining the size of the impeller and the inlet diameter, in relation to the installation for the preparation of liquid feed mixtures [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, it should be borne in mind that some of the premises have different capacities for livestock [6,7,8].…”
Section: Theoretical Methodological and Empirical Basementioning
confidence: 99%
“…A study of installations based on vane pumps [1,2,3,4,5,6,7,8], it was found that the rotational speed n from 1750 to 3000 min -1 is not always effective, although even with these values high performance indicators. Therefore, in experimental studies, we proceed from the fact that we take synchronous speeds of rotation of the electric motor (respectively, it will be the same for the impeller) n = 750, 1000 and 1500 min -1 , but for more accurate readings we take a step of 250 min -1 , respectively, points will be next n=750, 1000, 1250, 1500 and 1750 min -1 .…”
Section: Theoretical Methodological and Empirical Basementioning
confidence: 99%
“…The experimental part was carried out on a specially designed stand [2,3,4], which allows sampling in two modes: continuous and periodic.…”
Section: Theoretical Methodological and Empirical Basementioning
confidence: 99%